Technology ethics a philosophical introduction and readings - Robson, Gregory J.; Tsou, Jonathan Y. (New York, NY Routledge, 2023)
The first of its kind, this anthology in the burgeoning field of technology ethics offers students and other interested readers 32 chapters, each written in an accessible and lively manner specifically for this volume. The chapters are conveniently organized into five parts: Perspectives on Technology and its Value Technology and the Good Life Computer and Information Technology Technology and Business Biotechnologies and the Ethics of Enhancement A hallmark of the volume is multidisciplinary contributions both (1) in "analytic" and "continental" philosophies and (2) across several hot-button topics of interest to students, including the ethics of autonomous vehicles, psychotherapeutic phone apps, and bio-enhancement of cognition and in sports. The volume editors, both teachers of technology ethics, have compiled a set of original and timely chapters that will advance scholarly debate and stimulate fascinating and lively classroom discussion. Downloadable eResources (available from www.routledge.com/9781032038704) provide a glossary of all relevant terms, sample classroom activities/discussion questions relevant for chapters, and links to Stanford Encyclopedia of Philosophy entries and other relevant online materials. Key Features: Examines the most pivotal ethical questions around our use of technology, equipping readers to better understand technology's promises and perils. Explores throughout a central tension raised by technological progress: maintaining social stability vs. pursuing dynamic social improvements. Provides ample coverage of the pressing issues of free speech and productive online discourse
Includes bibliographical references and index.
Keywords: Technology -- Moral and ethical aspects